Modelling the Impact of RCEP Agreement on the Economic and Trade Environment of Beijing - Yuanqing Liu; Xiongying Chen; Yuan Tian (Discrete Dynamics in Nature and Society)
As a national economic, political, and cultural center that ranks first in terms of openness to the outside world, the signing of the RCEP agreement has undoubtedly brought a series of opportunities and challenges to Beijing. Based on the analysis of the two main features embodied in the RCEP agreement, this paper precisely analyzes the areas where the RCEP agreement has a key impact on Beijing’s economy and trade and points out the opportunities and challenges brought by the RCEP agreement to Beijing’s economic and trade development.